The influence of non-steroidal anti-inflammatory drugs and paracetamol used for pain control of orthodontic tooth movement: a systematic review - CORRÊA,ADRIANO S. (2017)
ABSTRACT The present study aimed to perform a systematic literature review to determine if there is a non-steroidal anti-inflammatory drug (NSAID) that interferes less within tooth movement. This research was performed according to the PRISMA statement. Articles were searched in eight electronic databases (PubMed, Scopus, Embase, Web of Science, LILACS, SciELO, Google Scholar, and Open Grey). Only experimental studies on male Wistar rats were selected, which included experiments related to the influence of NSAIDs on orthodontic movement. Studies in animals with pathological conditions, literature review articles, letters to the editor and/or editorials, case reports, abstracts, books, and book chapters were excluded. Each of the steps of this systematic literature review was performed by two examiners independently. Results: the total sample consisted of 505 articles, from which 6 studies were eligible after a qualitative analysis. From the drugs assessed, paracetamol was unanimous for not interfering within orthodontic movement when compared to the control group. However, drugs such as aspirin, ibuprofen, sodium diclofenac, and selective cyclooxygenase-2 inhibitors caused a reduction in tooth movement when compared to the control group. Conclusion: paracetamol could be considered the drug of choice for pain relief because it interferes less within tooth movement.